Р. DESCARTES: PRINCIPLES OF RATIONALISTIC METHOD AND MORALITY (TO THE QUESTION ON THE METHODS OF SCIENTIFIC RESEARCH IN THE FIELD OF PHILOSOPHY AND SOCIAL WORK) - Оксана ОСЕТРОВА (Епістемологічні дослідження у філософії, соціальних і політичних науках)
In this article, the focus of research attention is directed at understanding the principles of the deductive rationalist method of the French thinker of the New Age, R.Descartes, who formulated the rules of morality on its basis. The work involves a critical analysis of these principles, in particular morality, given the current conditions of existence, marked by social cataclysms that cause tragic changes and difficult life circumstances, the search for ways to minimize/overcome which should be directed by modern scientific research, which is currently being developed in the field of philosophy and social work. The purpose of this study is to provide a philosophical critical analysis of the key principles of the rationalist method of cognition and the maxims built on its basis, proposed by R. Descartes for personal discretion. In addition, the paper focuses on those obstacles that, by obscuring the common sense of an individual, lead to the non-obviousness of the ocular, which results in the establishment and further adherence to a false conclusion instead of the true one, which will be facilitated by the use of the psychoanalytic method of research. The achievement of this goal will contribute to the formation of critical thinking in novice scientists, which, based on doubt, should ultimately be directed not at denial and removal, which is irrational destruction, but at achieving and comprehending the truth, which should be the basis for finding constructive solutions in such meaningful areas of human activity as philosophy and practical social work. The analysis made it possible to identify the following important points:1. In terms of ratio: special attention should be paid to understanding the essence of the first principle of R.Descartes’ rationalist method, which provides for a comprehensive scientific justification for the choice of simple and obvious truths as the basis for further development of scientific research, which will refute the non-obviousness of the obvious, as well as a careful approach to identifying keywords within it. 2. In terms of morality: a scientist should develop determination, firmness, and perseverance, which, despite doubts, will allow him or her to follow his or her own individual scientific trajectory. In the future, this work should focus on the conscious choice and use of methods of cognition, which will help to improve the efficiency of research activities and the quality of work of beginning scientists.